2023
DOI: 10.3847/1538-4357/acdd57
|View full text |Cite
|
Sign up to set email alerts
|

Active Galactic Nuclei Feedback in SDSS-IV MaNGA: AGNs Have Suppressed Central Star Formation Rates

Caleb Lammers,
Kartheik G. Iyer,
Hector Ibarra-Medel
et al.

Abstract: Despite the importance of feedback from active galactic nuclei (AGNs) in models of galaxy evolution, observational constraints on the influence of AGN feedback on star formation remain weak. To this end, we have compared the star formation trends of 279 low-redshift AGN galaxies with 558 inactive control galaxies using integral field unit spectroscopy from the Sloan Digital Sky Survey-IV Mapping Nearby Galaxies at Apache Point Observatory survey. With a Gaussian-process-based methodology, we reconstruct nonpar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 153 publications
0
1
0
Order By: Relevance
“…Despite this localised positive feedback, the simulations show that the outflows reduce the surface density of star formation across the galaxy (i.e., negative feedback) by limiting the availability of gas rather than evacuating it [213,267]. Recent observational work using data from legacy integral field spectroscopic surveys report evidence for suppressed gas fractions and SFRs in the central kiloparsec of galaxies hosting AGN as compared to matched controls (e.g., [268][269][270]).…”
Section: Localised and Transient Impact On Gas And Star Formationmentioning
confidence: 90%
See 1 more Smart Citation
“…Despite this localised positive feedback, the simulations show that the outflows reduce the surface density of star formation across the galaxy (i.e., negative feedback) by limiting the availability of gas rather than evacuating it [213,267]. Recent observational work using data from legacy integral field spectroscopic surveys report evidence for suppressed gas fractions and SFRs in the central kiloparsec of galaxies hosting AGN as compared to matched controls (e.g., [268][269][270]).…”
Section: Localised and Transient Impact On Gas And Star Formationmentioning
confidence: 90%
“…Similar comparisons between the observations of the overall galaxy population and simulations will be important to further test and refine the different prescriptions of feedback models in simulations (e.g., [314,315]). The spatially resolved measurements of star formation, and stellar populations, on large samples of galaxies in different environments, can shed further insight into the quenching process and the potential role of AGN across different populations (e.g., [270,316]).…”
Section: Global and Long-term Cumulative Impact Of Agn Feedbackmentioning
confidence: 99%
“…The Seyfert galaxy NGC 4051 shows the signature of multiple jet episodes [112,113], as well as a hole with a diameter of ∼10 parsecs in its molecular gas distribution [114]. A recent MaNGA study [115] suggested that AGN feedback can significantly affect central star formation, but may be inefficient in driving galaxy-wide quenching in low-redshift galaxies. These studies showed that a detailed study of low-power AGN outflows, molecular gas, and star formation in radio-quiet galaxies with high resolution is important to understand feedback processes and their time scales.…”
Section: Episodic Agn Activity and Feedback: Ngc 2639mentioning
confidence: 99%